D8 – Public Lecture material - Agapiou, Athos (My University, 2026)
This document presents the materials and activities developed within Deliverable D8, focusing on public lectures and outreach actions aimed at engaging the wider public, students, and non-specialized audiences. The deliverable supports the dissemination and communication objectives of the CONNECTING project by promoting awareness of its goals, technologies, and impact on cultural heritage research. Public lectures have been organized to present the project’s mission, including the use of advanced technologies such as VTOL drones, RGB, multispectral, and hyperspectral imaging, and ground-based laser scanning for the detection, monitoring, and documentation of cultural heritage sites. These events aim to make scientific knowledge accessible and stimulate public interest in cultural heritage preservation. The deliverable includes a collection of dissemination materials such as presentations, posters, and supporting content used during lectures and outreach events (e.g., Researchers’ Night and similar initiatives). All materials acknowledge the CONNECTING project and help increase its visibility and societal impact. Through these activities, the project strengthens its connection with the public, fosters knowledge exchange, and enhances the potential for exploitation of its results beyond the scientific community.
Keywords: Communication; Dissemination; Exploitation; Cultural Heritage